Environmental and ethical–moral contributions of a Wampis ancestral narrative - Yóplac-Acosta, Manuel (2023)
This work interprets the wampis ancestral narrative “Ya najanakmau” or “the origin of the stars” and reflects on its contributions to the environmental and ethical-moral conception. It is based on the idea that ancestral oral narratives contain valuable knowledge as a result of the long balanced coexistence of the wampis man with the Amazon. Interculturality and ecology of knowledge are taken as theoretical foundations; and for interpretation, diatoptic and analogical hermeneutics are used as methods. The results suggest that the environmental contribution of the narrative conceives nature as a whole that has the category of subject where life develops; as well as the reflection that what is bad is harmful and must be rejected for the coexistence of a balance, from an ethical-moral perspective and contribution.